An exploration of alcohol advertising on social networking sites: an analysis of content, interactions and young people's perspectives. (4th March 2017) - Atkinson, Amanda Marie; Ross-Houle, Kimberley May; Begley, Emma; Sumnall, Harry
Abstract: Young people increasingly communicate and interact via social digital media such as Social Network Sites (SNS), where they discuss and display alcohol-related content. SNS have also become an important aspect of the alcohol industry's multi-platform marketing strategies, which may contribute to the creation of intoxigenic digital spaces in which young people learn about alcohol. This paper presents findings of a content analysis of the extent, nature, and user interaction with SNS-based alcohol marketing for brands popular among young people in the UK. It provides a systematic analysis of both official and user generated marketing content on brand Facebook and Twitter profiles, and user interaction with such content. Findings from peer group interviews ( N  = 14) also present young people's ( N  = 70) perspectives and experiences regarding alcohol marketing on SNS. New SNS engagement marketing strategies extended existing multi-platform brand marketing. Young people interacted with such strategies as part of their identity-making practices, yet through a discourse of immaturity distanced themselves from certain brands, online marketing practices and the idea that their own actions were influenced by marketing. Local night life economy marketing appeared more meaningful and relevant to young people and led to further interaction with brand marketing. Implications of the findings are discussed in relation to the influence of alcohol marketing on young people, and the implications for current regulatory frameworks.